Prevalence and Antimicrobial Resistance Patterns of Urinary Tract Infections in Neonates with Late Onset Sepsis - Naheed Haroon Kazi; Amanullah Lail; Sadaf Saeed Shami; Huma Qureshi; Amanullah Memon; Farukh Imtiaz Bhanbhro, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: This research looks at how common urinary tract infections (UTIs) are in neonate with late-onset sepsis (LOS) in Pakistan and how these infections respond to antibiotics. Since neonatal sepsis is a major cause of neonate deaths and UTIs can lead to sepsis, the study aims to find effective antibiotics for treating drug-resistant infections. This will help reduce illness, hospital readmissions, and the length of hospital stays. The results are meant to support doctors in making better treatment decisions and improving care for neonates with UTIs. Objective: To establish the prevalence and patterns of antibiotic sensitivity of urinary tract infections (UTIs) among neonates with late-onset sepsis Study design: A cross-sectional and observational analysis Duration and place of study: This study was conducted in Muhammad Medical College Hospital Mirpurkhas from December 2023 to December 2024 Methodology: This cross-sectional observational study involved 120 newborns, 7 to 28 days old with late-onset sepsis, selected through non-probability sampling. An informed consent, demographic data were captured, and catheterized urine samples under aseptic precautions were collected for culture and sensitivity. UTIs were defined as the growth of a single organism at ≥10,000 CFU/mL. CLSI standards were employed to determine antibiotic sensitivity. Data were analyzed using SPSS 25, qualitative variables reported as frequencies and percentages and quantitative variables as means and standard deviations. Chi-square tests were used to test associations, and p-values of ≤ 0.05 were taken as significant. Results: Around 120 neonates were a part of this study who were aged from 7 days to 28 days maximum. The mean age calculated was 27.25 days. The males were in majority. There were a total of 92 males (76.7%) and 28 females (23.3%). The mean weight calculated was 1.9 kg. Among these 120 cases, 16.7% (n=20) cases were of sepsis that were reported due to UTI. Conclusion: The research shows that E. coli is the most frequent bacterium in neonatal UTIs, which has various resistance and sensitivity to commonly prescribed drugs.